Immune Responses and Egg Productions of Quails Fed Rations Supplemented with Larvae Meal of Black Soldier Fly (Hermetia illucens) - Harlystiarini Harlystiarini; R. Mutia; I. W. T. Wibawan; D. A. Astuti (Tropical Animal Science Journal, 2020)
The larvae of black soldier fly/BSF (Hermetia illucens) seems to be a considerable material as an alternative to antibiotic growth promoters (AGPs) since they are rich in antimicrobial peptides (AMPs) and lauric acid that can improve the health and immune response. This study aimed to evaluate the effect of BSF larvae meal as a replacement of fish meal on production performances, health status, and immune response of quails. The experimental design using completely randomized design consisted of 3 treatments of dose of BSF larvae meal i.e., R0: ration without supplementation of BSF larvae meal; R1: ration supplemented with 6.57% BSF larvae meal to substitute 50% fish meal, and R2: ration supplemented with 13.15% BSF larvae meal to substitute 100% fish meal. The parameters observed were production performances, hematological profile, macrophage phagocytic activity and capacity, and antibody titer against the avian influenza virus. A completely randomized design was arranged with 3 treatments and 5 replications and data collected were analyzed by using one-way analysis of variance (ANOVA). The results showed that ration supplemented with 13.15% BSF larvae meal demonstrated significant effects on the enhancement of egg production and egg mass (p<0.05). Based on hematological profile, the health status of experimental quails was unaltered by the treatments, but immune response of quails fed ration supplemented with 13.15% BSF larvae meal was found to be significantly increased as revealed by the increased average macrophage phagocytic activity and capacity, as well as a higher antibody titer against avian influenza virus (p<0.05). It is concluded that black soldier fly (BSF) larvae meal can be used as an alternative substitution to fish meal up to 13.15%, based on the improvement of immune response and the increase in egg production of quails.